The Item (awaba) in Quran-Semantical Indication - Arman, لينا أحمد محمد; Al-Nuseirat, جهاد محمد (Dirasat: Shari'a and Law Sciences, 2022)
Objective: The study is concerned with the item (Awb) in the Holy Qur’an, through a contextual semantic study, which aims to follow the item (Awb) and what is close to it according to its occurrence in the Holy Qur’an, And knowing the relationship between the changes of the substance (Awb), and what was used of it, and what was neglected, also to reveal the semantics of the linguistic material, and to clarify its contextual implications in the Qur’anic usage. Methods: The study adopts the inductive and analytical approaches, by tracing the origins of the item in the dictionaries historically, and then monitoring its Occurrence in the different Qur’anic contexts, in order to elicit the different Connotations arising from this item. Result: The study found that the semantics of the linguistic, morphological, and grammatical terms fit the context in which they were mentioned, so it is not appropriate to replace them with other words, no matter how close they are. Conclustions: Taking care of semantic studies, and paying attention to collecting Quranic words with similar meaning in dictionaries for this purpose; to facilitate the work of scholars in the field of semantic studies.